Detection of blaOXA-1, blaTEM-1, and Virulence Factors in E. coli Isolated From Seals - Vale, Ana P.; Shubin, Lynae; Cummins, Juliana; Leonard, Finola C.; Barry, Gerald (Frontiers in Veterinary Science, 2021)
Marine mammals are frequently considered good sentinels for human, animal and environmental health due to their long lifespan, coastal habitat and characteristics as top chain predators. Using a One Health approach, marine mammals can provide information that helps to enhance the understanding of the health of the marine and coastal environment. Antimicrobial resistance (AMR) is the quintessential One Health problem that poses a well-recognized threat to human, animal and ecosystem health worldwide. Treated and untreated sewage, hospital waste and agricultural run-off are often responsible for the spread of AMR in marine and freshwater ecosystems. Recently, the isolation of New Delhi metallo-β-lactamase (NDM)-producing Enterobacteriaceae was reported for the first time in Europe, from both freshwater and seawater sampled on two Irish beaches located near an untreated human sewage ocean discharge. Rescued seals (n=25) were used as sentinels to investigate the levels of AMR in the Irish coastal ecosystem. Faecal swabs were collected from these animals and bacterial isolates (E. coli and cefotaxime-resistant non-E. coli) from each swab were selected for further investigation. E. coli isolates were characterized in terms of phylogenetic group typing, AMR and virulence factors. All E. coli isolates investigated in this study (n=39) were ampicillin resistant while 26 (66.6%) were multi-drug resistant (MDR). Resistance genes blaOXA-1 and blaTEM-1 were detected in 16 and 6 isolates, respectively. Additionally, virulence factors associated with adhesion (sfa, papA and papC) and siderophores (fyuA and iutA) were identified. An additional 19 faecal cefotaxime-resistant non-E. coli isolates were investigated for the presence of β-lactamase encoding genes. These isolates were identified as Leclercia adecarboxylata, Pantoea agglomerans and Enterobacter ludwigii, however, none were positive for the presence of the genes investigated. To the authors knowledge this is the first study reporting the detection of blaOXA-1 and blaTEM-1 in phocid faecal E. coli in Europe. These results highlight the importance of marine mammals as sentinels for the presence and spread of AMR in the marine and coastal environment.